Costos de la reforestación semi-mecanizada y manual en potreros de la Chontalpa, México: un estudio comparativo - Keyes Hennin, Michael R.; Anduaga Muñoz, Javier (Instituto de Ecología, A.C., 2016)
The comparative establishment costs of a semi-mechanized vs manual plantation were calculated for one hectare of rangelands with Tabebuia rosea and Cordia dodecandra. The semi-mechanized plantation method was 17% less costly and much faster when compared with the manual method of plantation establishment. In general, better survival or seedling growth attest to the biological superiority of the semimechanized plantation method. However, due to the high variability, although the semi-mechanized plantation method offered improved height growth, these differences were not always statistically significant.